Association Between Accumulation of Child Maltreatment and Salivary Oxytocin Level Among Japanese Adolescents - Mizuki, Rie; Fujiwara, Takeo (Frontiers in Pediatrics, 2021)
Background: Child maltreatment is related to oxytocin (OT), which is related to social functioning. It may hamper the OT level to avoid a harmful situation and increase the OT level to adapt to the situation using a tend-and-befriend stress reaction. Objective: This study aims to examine the association between the accumulation of moderate–severe childhood maltreatment and salivary OT levels in Japanese adolescents. Participants: We used convenience samples of adolescents living in an institution (n = 31) and those living with their parents (n = 46). Methods: Child maltreatment experiences were measured with the Childhood Trauma Questionnaire. The salivary OT levels were assessed by enzyme linked immunosorbent assay. A multivariate regression analysis was performed to see the association between the accumulation of child maltreatment types and the salivary OT levels adjusted for covariates (i.e., age, sex, and duration of institutionalization). Results: Physical abuse was associated with higher OT, while emotional neglect showed an inverse association with OT. OT was the lowest with one maltreatment type group, which was significantly lower than the non-maltreatment group. As the number of maltreatment types increased from one maltreatment type to 2-3 types and to 4-5 types, OT also increased. This U-shaped association between the number of maltreatment types and OT was confirmed with the significant result of a square term of number of maltreatment type in the model (p=0.012). Conclusion: We found herein a U-shaped association between the accumulation of child maltreatment and salivary OT levels. Also, different types of maltreatment had varied effects on the salivary OT. Further study is needed to elucidate the non-linear association between child maltreatment and OT levels.